Application Of Kolcaba Theory In Child Patients With Pain Problems In The Infection Room - Oktavia Karundeng, Jeni; Nurhaeni, Nani; Wanda, Dessie (Journals of Ners Community, 2022)
Pain is a health problem to consider especially for children and adolescents. Studies showed 15-35% of children in the nonclinical population suffered persistent and chronic pain. This study aims to provide an overview of the fulfillment of comfort needs in children with pain problems through the provision of Virtual Reality interventions. The application of Kolcaba's theory in providing nursing care for children with pain problems can provide holistic benefits and guide nurses in conducting systematic assessments. The application of virtual reality as an intervention in nursing care has also been proven to provide a sense of comfort and reduce pain and anxiety. The method used is a case study with a nursing care approach to 5 patients with pain problems aged > 10 years. The comfort level will be measured using the Comfort Behavior Checklist Scale. Cases were taken in the pediatric infection room of National Referral Hospital DR. Cipto Mangunkusumo.